Synthesis and Biological Evaluation of 5-Pyridine-4-(arylidine amino)-3-mercapto-4(H)-1,2,4-triazoles - BHANOJIRAO, M.E.; G. RAJURKAR, VIKAS (Asian Journal of Chemistry, 2010)
As triazoles have proven to be good antimicrobial agents, a new series of triazole derivatives were synthesized and characterized by 1H NMR, IR, GCMS sophisticated analytical instruments and were evaluated for their antimicrobial activity. Out of several derivatives synthesized a few of 5-pyridine-4-(arylidine amino)-3-mercapto-4(H)-1,2,4-triazoles showed good antimicrobial activity by using cup-plate method.